2019
DOI: 10.34190/ejise.19.22.2.003
|View full text |Cite
|
Sign up to set email alerts
|

Net Impacts in Front Office IS: a First Operationalization of Delone and McLean Model in the Banking Sector

Abstract: The variable Net Impacts, a key variable in the models for information systems evaluation, is rarely operationalized according to a rigorous method and never for the banking sector. DeLone and McLean (2016) note that the challenge of developing measures to evaluate information systems is still relevant. The measurement and conceptualization of variables in real contexts is both very important and relatively absent in the literature. This research aims at operationalizing the Net Impacts construct resulting fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…An information technology success can be measured through its impact on work at the users’ level ( Michel et al, 2019 ), and users’ outcomes can be dichotomized into psychological and behavioral outcomes ( Yavas and Babakus, 2010 ). This study is concerned with user’s behavioral outcomes illustrated by employee performance.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…An information technology success can be measured through its impact on work at the users’ level ( Michel et al, 2019 ), and users’ outcomes can be dichotomized into psychological and behavioral outcomes ( Yavas and Babakus, 2010 ). This study is concerned with user’s behavioral outcomes illustrated by employee performance.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…Therefore, the evaluation of the system quality is mostly measured by its ease of use perceptiveness, purpose, and consistency, the quality of the data, convenience, and the mixture pattern. Besides, it is also believed that only IS users are able to evaluate the system quality (Michel & Cocula, 2017). It is also reported that certain attributes or qualities such as valuable, reliability, the quality of the information, and the flexibility of the system can be assessed by system quality.…”
Section: The Relationship Between System Quality and Hrmis Satisfactionmentioning
confidence: 99%
“…They introduced the information system success model (ISSM), which is currently regarded as one of the key models for IS evaluation by the scientific community. However, businesses rarely use it [27]. Instead, they mention guidelines like ITIL, COBIT, or CMMI to guarantee the quality of IS, the monitoring of practices or the level of IS maturity, and even its governance [27].…”
Section: The Concept Of Net Impactsmentioning
confidence: 99%
“…However, businesses rarely use it [27]. Instead, they mention guidelines like ITIL, COBIT, or CMMI to guarantee the quality of IS, the monitoring of practices or the level of IS maturity, and even its governance [27]. ISSM, initially made up of five factors, is multidimensional, recognizing that both temporal and causal influences are necessary for IS to succeed as a built process [27] 171 model shows that information and system quality influence user happiness and IS use, which in turn effect individual impact.…”
Section: The Concept Of Net Impactsmentioning
confidence: 99%
See 1 more Smart Citation